Nanoparticle approaches for manipulating cytokine delivery and neutralization - Wang, Rui; Kubiatowicz, Luke J.; Zhang, Runhe; Bao, Lin; Fang, Ronnie H.; Zhang, Liangfang (Frontiers in Immunology, 2025)
Cytokines are crucial regulators of inflammation and immune tolerance, making them promising targets for treating immune-related diseases like cancer, infections, and autoimmune disorders. While cytokine-based therapies have shown potential, challenges such as dose-limiting toxicity and suboptimal pharmacokinetics have constrained their clinical success. Recent advancements in nanotechnology offer innovative solutions to these limitations, particularly through the use of nanoparticle-based platforms that enhance cytokine delivery and neutralization. This review begins by examining the landscape of cytokine delivery, emphasizing how it can be accomplished using nanoparticle systems encapsulating proteins, DNA or mRNA payloads. We then discuss recent progress on platforms for nanoparticle-based cytokine neutralization, including nanoparticle–antibody complexes and cell membrane-coated nanoparticles. Finally, we highlight the latest clinical developments in cytokine-based therapies employing these strategies before addressing the critical challenges ahead that need to be overcome in order to fully realize the therapeutic potential of nanoparticle-based cytokine manipulation.